Distribution of surface-active substances in the sea surface microlayers off the Malaysian peninsula - Mustaffa, Nur Ili Hamizah; Khairul Anuar, Ayu Nabila; Zaini, Nor Syafikah; Mohamed, Khairul Nizam; Latif, Mohd Talib (Elsevier, 2024)
The sea surface microlayer (SML), particularly in monsoon-influenced regions, remains largely unexplored. This study aims to determine the concentrations, enrichment, and factors controlling the enrichment processes of surface-active substances (SASs), which include surfactants, dissolved monosaccharides (MCHOs), polysaccharides (PCHOs), total dissolved carbohydrates (TDCHOs), and transparent exopolymer particles (TEPs) around the coastal area of Malaysian Peninsula. The SML samples and underlying water (ULW) from a depth of 1 m were collected during the southwest (August and September 2023) and northeast (November 2023) monsoons. Surfactants, TEPs, and dissolved carbohydrates were measured spectrometrically using methylene blue, the Alcian blue assay, and 2,4,6-Tri(2-pyridyl)-s-triazine (TPTZ), respectively. The results showed that stations influenced by anthropogenic activities were generally enriched with surfactants (Enrichment factor, EF = 1.40 ± 0.91) and carbohydrate species (TDCHOs = 1.38 ± 0.28, MCHOs = 1.54 ± 0.57, PCHOs = 1.85 ± 1.43). However, TEP enrichment was not observed in our study (EF = 0.68 ± 0.24). The SASs in the SML were correlated with their underlying concentrations, implying that transport from underlying water could be a major source of substances in the SML. High carbohydrate concentrations and enrichment were found during the northeast monsoon, implying that rain and runoff water affect concentrations in the SML. Besides, the enrichment of SASs persists at moderate wind speeds and is depleted at high wind speeds. © 2024